Parameters Affecting the Extraction Process of Jatropha curcas Oil Using a Single Screw Extruder - Siregar, Ali Nurrakhmad; Ghani, Jaharah A.; Che Haron, Che Hassan; Rizal, Muhammad (ITB Journal Publisher, LPPM ITB, 2015)
The most commonly used technique to separate oil and cake from J. curcas seeds is mechanical extraction. It uses simple tools such as a piston and a screw extruder to produce high pressure, driven by hand or by engine. A single screw extruder has one screw rotating inside the barrel and materials simultaneously flow from the feed to the die zone. The highest oil yield can be obtained by a well-designed oil press as well as finding the optimum conditions for all parameters involved during the extraction process. The influence of the parameters in a single screw extruder was studied using finite element analysis and computational fluid dynamics simulation with ANSYS POLYFLOW. The researchÂ focused on predictingÂ the velocity, pressure and shear rate in the metering section that influenced the screw rotational speed and mass flow rate. The obtained results revealed that increasing the screw rotational speed will increase the pressure, velocity and shear rate. Meanwhile, increasing the mass flow rate results in decreasing the pressure while the velocity and shear rate remain constant.